Inovação do design ergonômico na produção de vestuário para futsal - Maestá, Allan César (2015)
This work was based on research of technologies and materials, to create and develop a sport uniforms collection for soccer practice with an ergonomic design, through cutouts in modeling respecting the needs of practitioners , in addition to the application of different textile technologies such as technological fabrics and nanotechnology. Through target audience research it was possible to detect which tastes and desires of consumers and develop a collection of game uniforms, training and casual wear. Based on versatility, comfort, performance, and not least, aesthetics, job search bring news in the sports industry and encourage the practice of this sport.